2008
DOI: 10.1103/physrevb.78.224209
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the liquid and the crystal of the phase-change materialSnSe2: First-principles molecular dynamics

Abstract: First-principles molecular dynamics simulations are used to study the structural properties of liquid and crystalline SnSe 2. We reproduce the experimental structure factor with confidence and fully describe the pair-correlation functions and the local structure of the liquid. It is shown that, unlike other group IV chalcogenides such as GeSe 2 , SnSe 2 does not display tetrahedral ordering in the liquid and contains a large amount of fivefold tin atoms with selenium atoms lying in an equatorial plane and at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Moreover, the average number of valence electrons per atom was identified as an order parameter, with the octahedral‐to‐tetrahedral transition occurring at a threshold of about 4.25. Micoulaut et al46 noted that an isoelectronic exchange can also impact the occurrence of tetrahedral coordination as they changed the stoichiometry from SnSe 2 to GeSe 2 , although this preserves the number of valence electrons 47. Furthermore, an alternation between atomic species (e.g., ABAB) is observed in phase‐change materials, resembling features of the crystalline structures as discussed later 32.…”
Section: Structure and Bonding In The Crystalline And The Amorphoumentioning
confidence: 96%
“…Moreover, the average number of valence electrons per atom was identified as an order parameter, with the octahedral‐to‐tetrahedral transition occurring at a threshold of about 4.25. Micoulaut et al46 noted that an isoelectronic exchange can also impact the occurrence of tetrahedral coordination as they changed the stoichiometry from SnSe 2 to GeSe 2 , although this preserves the number of valence electrons 47. Furthermore, an alternation between atomic species (e.g., ABAB) is observed in phase‐change materials, resembling features of the crystalline structures as discussed later 32.…”
Section: Structure and Bonding In The Crystalline And The Amorphoumentioning
confidence: 96%
“…[ 11 ] It has been proposed that SnSe 2 can rapidly and reversibly switch from the amorphous to the crystalline state under laser heating, which leads to signifi cant changes in the optical refl ectivity and thus provides bright potential for data storage applications. [ 13 ] However, most studies have been reported on thick SnSe 2 fi lms obtained by radio-frequency (RF) magnetron sputtering, [ 14 ] or molecular beam epitaxy (MBE) deposition. [ 15 ] Recently reported mechanical exfoliated SnSe 2 crystals demonstrated that it has a high carrier mobility of 8.6 cm 2 V −1 s −1 in ambient environment, [ 16 ] superior to many other reported 2D materials.…”
Section: Doi: 101002/adma201503873mentioning
confidence: 99%
“…Under further compression, SnSe transforms to the B2 structure (P m3m space group) and this phase was found to exhibit a superconducting transition at low temperatures above 58 GPa [7]. SnSe 2 is also a layered semiconductor with a hexagonal CdI 2 -type crystal structure (P3m1 space group) [8]. From X-ray diffraction (XRD), it was found that SnSe 2 , which is important for photoelectric applications [9], shows a second polytype with a space group of R3m [10].…”
mentioning
confidence: 99%